Exploration dive finding the frogfish - Siti Rabiatull Aisha, Idris (2021)
A couple months back, my team and I went to Perhentian Island in Terengganu for a project called exploration dive. We were assisted by Mr Azharil Art from D’Lagoon Dive Centre, which was recommended by Mr Saiful Bahri Yakup, our team member who is a very well experienced diving instructor. We spent quite some time there with a few numbers of dive trip pursuing research related to marine life and the underwater environment. Nonetheless, this writing will only enumerate our work focusing on frogfish, including its behaviour, habitat, and species.